On Load Characteristic of the New Design Permanent Magnets Reluctance Generator - Andi Pawawoi; Syafii Syafii (International Journal of Applied Power Engineering (IJAPE), 2017)
These The new design of a permanent magnet reluctance generator claimed to be able to convert the energy of the permanent magnet is the source of the main field into electrical energy, so that the generator output power can reach 167% compared with the input power axis. In this paper will discuss the characteristics of the generator voltage when under load, pure resistance, inductive load and caThese The new design of a permanent magnet reluctance generator claimed to be able to convert the energy of the permanent magnet is the source of the main field into electrical energy, so that the generator output power can reach 167% compared with the input power axis. In this paper will discuss the characteristics of the generator voltage when under load, pure resistance, inductive load and capacitive load. The results showed that when given a purely resistive load, the terminal voltage tends to be constant, but if given the inductive load, the voltage drop occurs significantly approaching zero voltage at full load current. It is very different when loaded capacitive load. When the generator under load is capacitive, the generator voltage at full load increased by 224.7% from no-load voltage.pacitive load. The results showed that when given a purely resistive load, the terminal voltage tends to be constant, but if given the inductive load, the voltage drop occurs significantly approaching zero voltage at full load current. It is very different when loaded capacitive load. When the generator under load is capacitive, the generator voltage at full load increased by 224.7% from no-load voltage